Navigating Pretext and Legal Consequences on Stateless Indonesian Children in Malaysia - Intan, Adilla Meytiara (Syntax Literate, 2024)
Due to lack of job opportunity, low-skilled Indonesian workers opted to work in Malaysia in hope for a better opportunity. As migrant workers in a foreign country, Indonesian are obligated to follow a string of policies reserved for foreign worker. Legal problems started to arise when those workers started a family in Malaysia. According to our interviews with fifty Indonesian Worker in Kuala Lumpur and Indonesian Government Officials in the Embassy, they admitted their ignorance of the ramification of their actions, the risk of statelessness of their children. Indonesian workers are (1) marrying fellow Indonesian workers, (2) marrying foreign workers, (3) marrying Malaysian nationality. As the family grew, their children born in Malaysia may (1) be an Indonesian, provided that their parents marriage are registered, (2) be Malaysian, provided that their parents marriage is legitimate under Malaysian Marriage Law, (3) stateless. The purpose of this paper is to set out the legal ramifications following an Indonesian Workers’ marriage to eradicate statelessness of their children and provide solution for them to obtain Indonesian citizenship by combining normative and empirical method to achieve the result. This paper is a conclusion of STIH Adhyaksa’s community services in collaboration with Indonesian Embassy in Kuala Lumpur, Malaysia.